Stable Large‐Area (10 × 10 cm2) Printable Mesoscopic Perovskite Module Exceeding 10% Efficiency. Issue 2 (31st January 2017) - Hu, Yue; Si, Si; Mei, Anyi; Rong, Yaoguang; Liu, Huawei; Li, Xiong; Han, Hongwei
Abstract : The commercial manufacturing of perovskite solar modules (PSM) suffers from stability concerns and scalability issues. We demonstrate a hole‐conductor‐free printable solar module embodiment, which employs a triple layer of mesoporous TiO2 /ZrO2 /carbon as scaffold, and is infiltrated by a mixed cation lead halide perovskite (5‐AVA)x (MA)1−x PbI3 as a light harvester. Here, hole conductor or Au reflector are not employed, and instead, the back contact comprises simply a printed carbon layer. Upon optimizing the thickness alignment of the triple mesoscopic layer and the design of the active area, the unit cell shows 14.02% power conversion efficiency (PCE) under 100 mW cm −2 condition, while a larger area of 10 serially connected cells module (10 × 10 cm 2 ), shows a 10.4% PCE on an active area of 49 cm 2 . Light‐soaking stability of 1000 h has been demonstrated, as well as local outdoor stability of 1 month and a shelf‐life stability of over 1 year. This paves the way for the realization of efficient and stable large‐area PSMs for industrial deployment. Abstract : The low‐cost hole‐conductor free, printable mesoscopic perovskite solar cell with carbon counter electrode has been successfully up‐scaled to 100 cm 2, and achieved the highest PCE of 10.4%. A 7 m 2 fully printable perovskite solar panel is presented, showing reproducibility of screen‐printing technique in manufacturing of high‐performance perovskite solar modules. The modules show good stability under continuous illumination and in local outdoor environment.